Innovative Precision Gene‐Editing Tools in Personalized Cancer Medicine - Dai, Xiaofeng (Adv Sci (Weinh), 2020)
The development of clustered regularly interspaced short palindromic repeats (CRISPR) has spurred a successive wave of genome‐engineering following zinc finger nucleases and transcription activator‐like effector nucleases, and made gene‐editing a promising strategy in the prevention and treatment of genetic diseases. However, gene‐editing is not widely adopted in clinics due to some technical issues that challenge its safety and efficacy, and the lack of appropriate clinical regulations allowing them to advance toward improved human health without impinging on human ethics. By systematically examining the oncological applications of gene‐editing tools and critical factors challenging their medical translation, genome‐editing has substantial contributions to cancer driver gene discovery, tumor cell epigenome normalization, targeted delivery, cancer animal model establishment, and cancer immunotherapy and prevention in clinics. Gene‐editing tools, epitomized by CRISPR, are predicted to represent a promising strategy toward the precise control of cancer initiation and development. However, some technical problems and ethical concerns are serious issues that need to be appropriately addressed before CRISPR can be incorporated into the next generation of molecular precision medicine. In this light, new technical developments to limit off‐target effects are discussed herein, and the use of gene‐editing approaches for treating otherwise incurable cancers is brought into focus.